Impact of process parameters on printing resolution and dielectric properties of LTCC substrate. Issue 3 (1st July 2019) - Jasińska, Laura; Malecha, Karol; Szostak, Krzysztof; Słobodzian, Piotr
Abstract : Purpose: The low-temperature co-fired ceramics (LTCC) microfluidic-microwave devices fabrication requires careful consideration of two main factors: the accuracy of deposition of conductive paths and the modification needed to the standard process of the LTCC technology. Neither of them are well-described in the literature. Design/methodology/approach: The first part of this paper deals with the individual impact of screen parameters such as aperture, photosensitive emulsion thickness and mounting angle on the precision of the screen-printed conductive paths fabrication. For the quantitative analysis purposes, the design of experiment method with Taguchi orthogonal array and analysis of variance was used. The second part contains the characterization of the complex permittivity measured for different values of LTCC substrates lamination pressure. Findings: It can be concluded, that the combination of aperture, equal to 24 µ m, emulsion thickness 20 µ m and mounting angle 22.5° ensures the highest quality of printed conductive metallization. Furthermore, the obtained results indicate, that the modification of the lamination pressure does not affect significantly the dielectric parameters of the LTCC substrates. Originality/value: This paper shows two aspects of the fabrication of the microfluidic-microwave LTCC devices. First, the resolution of the applied metallization is critical in manufacturing high-frequency structures. The obtained experimental results have shown that optimal screen parameters, in terms of conductive pattern quality, can be found. Second, the received outcomes indicate that the changes in the lamination pressure do not affect significantly the electrical parameters of the substrate. Hence, this effect does not need to be taken into account.